Functions of Emojis in Indonesian College Students' Online Communication on Social Media X - Dewi, Amanda Kusuma; Sukaton, Ounu Zakiy (Alphabet, 2025)
With the advent of communication technology, emojis have become inseparable in online communication, acting as paralinguistic elements in written online communication. This study investigates how emojis contribute to online written communications and their prominent functions, specifically in Indonesian college students' communication observed from reply posts in the X automated base account, "@collegemfs," a communication hub for college students across Indonesia. This study utilized a mixed-method approach, a quantitative method to interpret the emoji functions, and a qualitative method to observe the most frequently used emojis and their functions. Results show that emojis contribute to online written communication in the community by reflecting the expressive, interpretative, and referential functions as primary functions, and the emphatic, politeness, structural, relational, and aesthetic functions as secondary functions. The most prominent functions found are the expressive primary function (60.8% of all data) and the emphatic secondary function (85.7% of all data), with the "loudly crying emoji" being the most prevalent emoji used in the community.